Review of phytochemical, pharmacological and socio-economic properties of Albertisia delagoensis (N.E.Br.) Forman (Menispermaceae): Ethnopharmacology of Albertisia delagoensis - Maroyi, Alfred (Ethnobotany Research and Applications, 2022)
Background: Albertisia delagoensis is a small shrub or liana which naturally occurs in open wooded grasslands in southern Africa. A critical appraisal of the phytochemical, pharmacological and socio-economic properties of A. delagoensis are provided. Methods: Research articles focusing on the phytochemical, pharmacological and socio-economic properties of A. delagoensis were mined from online databases such as Google Scholar, PubMed, Science Direct, SciELO and SpringerLink. No time limit was set for the search and all research outputs that aligned with the scope of the review were included. Results: Albertisia delagoensis has diverse uses as a food plant and also medicinal uses such as anthelmintic, improve sexual performance in men, and traditional medicine for back pain, body pains, chest pains, diarrhoea, hypertension, influenza, menstrual pain, sores and vomiting. Albertisia delagoensis exert biological activities such as antiplasmodial and cytotoxicity, and several phytochemical compounds such as cocsoline, cocsuline, cycleanine, dicentrine, O-methylcocsoline, roemrefidine, 3,4-dihydroxybenzoic acid, allantoic acid, nicotinic acid, phthalic acid and proto-quercitol have been isolated from the species. Conclusion: Many applications of A. delagoensis as source of food and herbal medicines as well as its phytochemistry and pharmarcological properties need further investigations. Keywords: Albertisia delagoensis, ethnomedicinal uses, indigenous knowledge, Menispermaceae, moonseed family